2022
DOI: 10.3389/fcvm.2022.1000846
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity is mitigated after a supervised exercise program in HER2-positive breast cancer undergoing adjuvant trastuzumab

Abstract: BackgroundTrastuzumab is used, alone or in conjunction with standard chemotherapy, to treat HER2-positive breast cancer (BC). Although it improves cancer outcomes, trastuzumab. can lead to cardiotoxicity. Physical exercise is a safe and effective supportive therapy in the management of side effects, but the cardioprotective effects of exercise are still unclear.ObjectivesThe primary aim of this study was to test whether trastuzumab-induced cardiotoxicity [left ventricular ejection fraction (LVEF) under 50%, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Although there is strong preclinical evidence for cardioprotection, 11 previous randomized trials of ExT during AC or human epidermal growth factor receptor 2–targeted therapy have failed to show a beneficial effect of ExT on cardiac function. 33,37–39 The improvements in cardiac function observed in our study may have been attributable to the higher dose and varied nature of the exercise stimulus (including high-intensity interval training). On the other hand, the lack of evidence for ExT-associated cardioprotection may be attributable to a historical reliance on resting measures of cardiac function (ie, LVEF and GLS).…”
Section: Discussionmentioning
confidence: 82%
“…Although there is strong preclinical evidence for cardioprotection, 11 previous randomized trials of ExT during AC or human epidermal growth factor receptor 2–targeted therapy have failed to show a beneficial effect of ExT on cardiac function. 33,37–39 The improvements in cardiac function observed in our study may have been attributable to the higher dose and varied nature of the exercise stimulus (including high-intensity interval training). On the other hand, the lack of evidence for ExT-associated cardioprotection may be attributable to a historical reliance on resting measures of cardiac function (ie, LVEF and GLS).…”
Section: Discussionmentioning
confidence: 82%
“…19,20,[36][37][38][39] Two studies have assessed the impact of 3-4 mo of aerobic ExT during HER2-targeted therapy. 40,41 In a single-arm study of BCS undergoing HER2-targeted therapy, Haykowsky et al 41 reported no impact of 4 mo of 3 sessions/wk of MCT on V ˙O2peak (+1.9 mL/kg/min, P = .2). In contrast, Jacquinot et al 40 reported that 12 wk of 3 sessions/wk of HIIT was associated with a 2.6 mL/kg/min improvement in V ˙O2peak .…”
Section: Ext and Crfmentioning
confidence: 99%
“…40,41 In a single-arm study of BCS undergoing HER2-targeted therapy, Haykowsky et al 41 reported no impact of 4 mo of 3 sessions/wk of MCT on V ˙O2peak (+1.9 mL/kg/min, P = .2). In contrast, Jacquinot et al 40 reported that 12 wk of 3 sessions/wk of HIIT was associated with a 2.6 mL/kg/min improvement in V ˙O2peak . The lack of V ˙O2peak improvement seen with the study of Haykowsky et al 41 may relate to the smaller sample size (n = 17 41 vs n = 75 40 ) and relatively modest adherence (60% of sessions attended 41 ).…”
Section: Ext and Crfmentioning
confidence: 99%
See 2 more Smart Citations